Learning styles, reading strategies and achievement among Iranian EFL male high school seniors in computer- based and face-to-face learning modes - Moharrer, Zahra (2015)
The infusion of technology into teaching and learning environments has compelled educators and material designers to refocus their attention on new educational paradigms to successfully use computers in conventional Face-To-Face (FTF) classrooms. Accordingly, the Iranian education system has pursued the trend of using computers,especially at secondary school level, to help students to cope with their learning problems independently. This study explored the effect of two independent variables namely learning style preferences and awareness of metacognitive reading strategies of Iranian senior high school male students on the dependent variable of their English lesson achievement scores. The Reading Proficiency (RP) of the students was also determined on the basis of their scores on the standardized Test of English as a Foreign Language (TOEFL©). Three RP levels were used later as moderator variables to explore the moderation effect on the relationship between learning styles and the English lesson achievement scores, and reading strategies and the English lesson achievement scores in the two instructional formats, that is, Computer-Based Learning (CBL) and FTF contexts. The CBL students were a group of senior high school male students who studied at a distance education center in Shiraz, Iran. Due to some problems such as the lack of high Internet speed in all parts of the province, Fars, the distance education center has provided the CBL students with interactive multimedia CD-ROMs which could be used everywhere. Some other difficulties like the lack of access to the CBL students, the only available technological distance education center which offered services for males, lack of cooperation on the part of the authorities due to the researcher‘s gender, and the shortage of time at the senior level since they were extremely busy preparing for the National Entrance Examination had made the researcher to use various types of sample selection, including simple random sampling, stratified random sampling, cluster random sampling, and purposive non-probability sampling. The purpose of this study was to determine the differences between dimensions of learning style preferences, metacognitive reading strategies, and the English lesson achievement scores and their relationships with each other while the three RP levels were chosen as a moderator variable. A total number of 236 EFL male high school seniors were selected from both the CBL and FTF contexts from different educational districts in Shiraz, Iran. The study administered the ex-post facto research design to explore whether the CBL students fine-tuned their learning styles to the newly engaged educational context and whether they performed differently compared to their counterparts in the FTF group. Various instruments were employed to collect data including Willing‘s (1988) questionnaire of learning style preferences, Anderson‘s (2003) Online Survey Of Reading Strategies (OSORS) questionnaire, a demographic questionnaire, TOEFL© Test, and an achievement test on the English course. The data were analyzed by using the AMOS software for Confirmatory Factor Analysis and Multigroup Path Analysis while the three RP levels were chosen as a moderator variable to investigate the interaction effects of RP on the relationships between learning style and achievement scores as well as awareness of metacognitive reading strategies and achievement scores. Descriptive statistics and Independent Samples t-test were conducted using the SPSS software. The results indicated that the most preferred to the least preferred learning styles among the FTF students were the communicative learning styles followed by authority-oriented,concrete, and analytical learning styles respectively. However, the most preferred to the least preferred learning styles among the CBL students were concrete followed by authority-oriented, analytical, and communicative learning styles. On the other hand, the most to the least dominant metacognitive reading strategy types used by the CBL students were problem solving, global, and support reading strategies, and of the FTF tudents, support, global, and support reading strategies. In addition, the mean score of the English lesson achievement scores in the CBL context was higher than that of the FTF context. Due to the CBL students‘ self-report of using CD-ROMs less frequently per week, their higher achievement scores might indirectly be influenced by their higher reading proficiency, having more experience in learning English outside the school, and more familiarity with software, hardware, or Internet use. The findings obtained from Multigroup Path Analysis indicated that there were statistically significant correlations between the overall preferences of learning styles and achievement scores in both the CBL and FTF learning environments. Reading proficiency could, in addition, affect the relationships significantly in the two pairwise comparisons of medium and high RP levels in the CBL context and only one of the pairwise of the high RP level in the FTF context. Nonetheless, there was no moderation effect of these RP levels because of the violation of the Critical Ratio criteria (CR > ± 1.96); therefore, the relationship between learning style preferences and achievement scores could not be moderated by any of the three RP levels in neither of the learning contexts. Employing the same statistical procedures for metacognitive reading strategies,it was found that there were significant relationships between the overall metacognitive reading strategies and achievement scores in both the CBL and FTF contexts. More specifically, reading proficiency could influence these relationships significantly in the two pairwise comparisons of medium and high RP levels in both the CBL and FTF contexts. However, the medium and high RP levels in the CBL context could have the moderator effects on the relationships between the overall metacognitive reading strategy awareness and achievement scores. However, there was only the moderation effect of high RP level on the relationships, but not the medium RP level due to the violation of the Critical Ratio criteria (CR > ± 1.96), in the FTF context. The findings of the current study indicate that introducing the use of computers in Iranian raditional classrooms is important. They also reveal that classroom practice should be concerned with accommodating students‘ preferences of learning styles in the both contexts. Furthermore, this study also shows that pedagogical practices should be modified to help students adjust their reading strategies to successfully plan, monitor,and evaluate themselves in both contexts.